DAMPAK PEMBIAYAAN BANK SYARIAH INDONESIA TERHADAP PEMBANGUNAN EKONOMI BERKELANJUTAN - Ayu Hani Marsani Tanjung; Risa Adelila Hasibuan; Sherin Aulia Putri; Muhammad Ikhsan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Sustainable economic development aims to balance economic growth, social welfare, and environmental preservation. In the Islamic economic context, Islamic banks are not only profit-oriented but also serve as instruments for public welfare. This study aims to analyze the impact of Islamic bank financing on sustainable economic development through a case study at Bank Syariah Indonesia (BSI) Krakatau Branch, Medan. The research uses a qualitative descriptive approach through interviews, observation, and literature review. Primary data were obtained from interviews with three financing clients and one financing officer, while secondary data were collected from BSI reports, OJK publications, and academic literature. The findings show that Islamic financing positively impacts community economic growth, MSME empowerment, and environmentally friendly financing (green financing). The musyarakah and mudharabah contracts enhance business productivity and welfare, while social programs such as qardhul hasan strengthen social solidarity. However, challenges remain in the dominance of consumptive financing and low Islamic financial literacy. Therefore, Islamic financing should be continuously developed in accordance with maqashid al-syariah principles to achieve an inclusive and sustainable economy.